Design of technology for the rye-wheat bread “Kharkivski rodnichok” with the addition of polyfunctional food additive “Magnetofооd” - Tsykhanovska, Iryna; Evlash, Victoria; Alexandrov, Alexandr; Lazarieva, Tetiana; Svidlo, Karina; Gontar, Tatуana (Eastern-European Journal of Enterprise Technologies, 2017)
We investigated effect of the polyfunctional food additive “Magnetofооd” on the physical-chemical, technological and organoleptic indicators of rye-wheat dough and finished products – the bread “Kharkivski rodnichok” and the bread “Darnitsky”. The impact of food additive “Magnetofооd” on the duration of dough fermentation was examined. It was proven that adding the food additive “Magnetofооd” reduces the time of dough fermentation by 10.0–16.7 % (for the dough prepared using wheat flour of grade 1 and pressed yeast), and by 7.1–14.3 % (for the dough prepared using wheat flour of grade 2 and pressed yeast with low amylolytic activity). We established positive effect of the food additive “Magnetofооd” on physical-chemical and technological indicators of rye-wheat semi-finished product and finished product. Introducing the additive to rye-wheat dough reduces moisture content and acidity by 1.0 % and 2.7–4.0 %, respectively (for the dough prepared using wheat flour of grade 1 and pressed yeast); by 5.8 % and by 7.1–8.2 %, respectively (for the dough prepared using wheat flour of grade 2 and pressed yeast with low amylolytic activity). It was determined that the higher yield of dough (by 2.1–3.7 %), and of the finished bread “Kharkivski rodnichok” and “Darnitskiy” (by 3.3–3.6 %), was obtained in samples with the addition of polyfunctional food additive “Magnetofооd”. It was found that the food additive “Magnetofооd” not only slows down the process of hydrolysis of hydrocarbon and protein components of dough (the accumulation of free organic acids), but also sorbs on Fe3О4 particles a certain amount of organic acids, which improves the quality of dough and finished product. It was established that adding “Magnetofооd” in the production of rye-wheat bread improves its organoleptic indicators: taste, color, porosity and crumb state. Based on the data obtained, we designed a technology for the rye-wheat bread “Kharkivski rodnichok” with the addition of polyfunctional food additive “Magnetofооd”